Swimmers somatotype profile - Leko, G.; Siljeg, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Morphological structure plays an important role in competitive swimming. Creating a large propulsive force with minimal frontal resistance ensures maximum swimming speed. It is therefore very important to achieve the optimum relationship between muscle mass and adipose tissue in order to achieve maximum results. The aim of this research was to determine the somatotype profiles of 14- 16-year-old male swimmers. Methods: In that regard, 68 swimmers from swimming clubs in Zagreb were examined using 10 anthropometric measurements that were subsequently used to determine the somatotype according to the method proposed by Heath and Carter. Results: and discussion The results point towards somewhat increased body fat percentage in comparison to swimming population. The somatotype of the examined swimmers indicates strong ectomorphic (3,31) component while the endomorphic (2,21) and messomorphic (2,34) components are similar in their values. The results indicate that all swimmers evaluated in this research have not completed their pubertal development and that the significant positive relationship can be evident only in the messomorphic component which is characterized by larger muscle mass and butterfly technique which is the most demanding in terms of energy expenditure.